The Patterns and Drivers of Bacterial and Fungal β-Diversity in a Typical Dryland Ecosystem of Northwest China - Wang, Jianming; Zhang, Tianhan; Li, Liping; Li, Jingwen; Feng, Yiming; Lu, Qi (Frontiers in Microbiology, 2017)
Dryland ecosystems cover more than 30% of the terrestrial area of China, while processes that shape the biogeographical patterns of bacterial and fungal β-diversity patterns have rarely been evaluated synchronously. To compare the biogeographic patterns and its drivers of bacterial and fungal β-diversity, we collected 62 soil samples from a typical dryland region of northwest China. We assessed bacterial and fungal communities by sequencing bacterial 16S rRNA gene and fungal ITS data. Meanwhile, the β-diversity was decomposed into two components: species replacement (species turnover) and nestedness to further explore the bacterial and fungal β-diversity patterns and its causes. The results show that both bacterial and fungal β-diversity were derived almost entirely from species turnover rather than from species nestedness. Distance-decay relationships confirmed that the geographic patterns of bacterial and fungal β-diversity were significantly different. Environmental factors had the dominant influence on both the bacterial and fungal β-diversity and species turnover, however, the role of geographic distance varied across bacterial and fungal communities. Furthermore, both bacterial and fungal nestedness did not significantly respond to the environmental and geographic distance. Our findings suggest that the different response of bacterial and fungal species turnover to dispersal limitation and other, unknown processes may result in different biogeographic patterns of bacterial and fungal β-diversity in the drylands of northwest China. Together, we highlight that the drivers of β-diversity patterns vary across between bacterial and fungal communities, and microbial β-diversity are driven by multiple factors in the drylands of northwest China.